Improved photoluminescence property of CTAB assisted polyaniline-AlZnO nanocomposite - Mitra, M. (American Institute of Physics Inc., 2015)
Polyaniline-Al doped ZnO ((PANI-AlZnO:: 70:30) nanocomposite was prepared via in situ chemical oxidative polymerization, while the hexagonal powder of AlZnO was synthesized via sol-gel technique, using Hexadecyltrimethylammonium bromide (CTAB) as a capping agent. The prepared nanocomposite was characterized by High resolution transmission electron microscopy (HRTEM), EDAX, X-ray diffraction (XRD) and Fourier transforms infrared (FTIR) spectra. The optical property of the nanomaterials is examined by photoluminescence (PL) spectra analysis. The XRD pattern confirms the formation of Al doped ZnO as well as PANI. The HRTEM images of the composite showed the formation of hexagonal AlZnO embedded in polyaniline matrix. EDAX spectrum shows the compositional analysis of the nanocomposite. FTIR spectra confirm the formation of nanocomposite of PANI and hexagonal AlZnO. The PL intensity of the nanocomposite is improved as compared to pure AlZnO. Â© 2015 AIP Publishing LLC.